The reliability of the Extra Load Index as a measure of relative load carriage economy. Issue 9 (2nd September 2017) - Hudson, Sean; Cooke, Carlton; Lloyd, Ray
Abstract: The aim of this study was to measure the reliability of the extra load index (ELI) as a method for assessing relative load carriage economy. Seventeen volunteers (12 males, 5 females) performed walking trials at 3 km·h −1, 6 km·h −1 and a self-selected speed. Trial conditions were repeated 7 days later to assess test–retest reliability. Trials involved four 4-minute periods of walking, each separated by 5 min of rest. The initial stage was performed unloaded followed in a randomised order by a second unloaded period and walking with backpacks of 7 and 20 kg. Results show ELI values did not differ significantly between trials for any of the speeds ( p = 0.46) with either of the additional loads ( p = 0.297). The systematic bias, limits of agreement and coefficients of variation were small in all trial conditions. We conclude the ELI appears to be a reliable measure of relative load carriage economy. Practitioner Summary: This paper demonstrates that the ELI is a reliable measure of load carriage economy at a range of walking speeds with both a light and heavy load. The ELI, therefore, represents a useful tool for comparing the relative economy associated with different load carriage systems.